ARTISANAL SHARK AND RAY FISHERIES IN SOUTH OF INDONESIA - Dharmadi, -; Fahmi, -; Sumadhiharga, Kurnaen (Marine Research in Indonesia, 2008)
Studies on artisanal fisheries of sharks and rays in Indonesia were carried out during 2001-2004. A market sampling method was employed to collect fisheries data from a number of major landings sites, namely: Pelabuhanratu and Cilacap in south coast of Java, Kedonganan in south coast of Bali and Tanjung Luar on the island of Lombok. Large proportions of the shark and ray landings were by-catch of tuna longlines and gillnets, and shark surface and bottom longlines from Tanjung Luar - east of Lombok. The shark landings were dominated by the families Carcharhinidae, Squalidae, Allopidae and Sphyrnidae, while rays were dominated by the Dasyatidae, Rhynchobatidae and Mobulidae. Most of the landings were processed to be dried and salted products for local consumptions. Some of them are exported to Asian countries. The most valuable part of sharks are their fins, which are a delicacy in Chinese cuisine. The major importers of Indonesian shark fins are Hongkong that contributed 46.3% of the total reported exports of shark fins from Indonesia.